Employment, Income, Health Insurance, Accessibility to Healthcare Facility, Age, and Prenatal Anxiety in Indonesia - Nur Fithriyanti Imamah; Nopryan Ekadinata; Galih Prayogo; Bayu Anggileo Pramesona (Universitas Aisyah Pringsewu, 2023)
Most of pregnancy women experience anxiety during pregnancy, both of in high-income and low-middle income countries. Financial security supported by the easiness access to the healthcare facility were important to the antenatal anxiety. Mother’s age, mother’s and husband’s working status will decrease anxiety in facing delivery. This study aimed to examine the effect of socioeconomic factors including working status, family income, health insurance, accessibility to the healthcare facility, and mother’s age to the prenatal anxiety of women in Indonesia. This study was a cross-sectional study conducted between April-May 2022 to examine the effect of socioeconomic factors to the prenatal anxiety. 155 pregnancy women in a Maternal Clinic participated in this study, chosen used consecutive sampling. Multiple linear regression has been used to explore the predictive and protective factors related to the prenatal anxiety. Majority of mother and husband’s age were 20-35 years old, with most of them graduated from Senior High School. Mother dominated mother’s working status without employment and or housewives while husband worked in non-government institutions. Only few of mother used the private insurance as their healthcare insurance and public transportation to go to the healthcare facility. Two of socioeconomic factors found significantly affected the prenatal anxiety including the distance to access the healthcare facility (.020, B: -.163) and wife’s age (.000, B: -.510). The distance between residence to the healthcare facility and mother’s age were socioeconomic factors affected the prenatal anxiety. Other factors could help mother have better preparation in pregnancy and facing delivery.Abstrak: Mayoritas Ibu hamil mengalami kecemasan selama kehamilan, baik pada negara-negara dengan pendapatan tinggi dan menengah ke bawah. Keamanan keuangan didukung dengan kemudahan dalam mengakses fasilitas kesehatan penting bagi kecemasan sebelum persalinan. Usia ibu, status bekerja Ibu dan suami akan membantu menurunkan kecemasan menghadapi persalinan. Penelitian ini bertujuan untuk menguji pengaruh faktor sosial dan ekonomi yang terdiri dari status bekerja, pendapatan keluarga, asuransi kesehatan, akses terhadap fasilitas kesehatan, dan usia Ibu terhadap kecemasan persalinan Ibu di Indonesia. Penelitian ini merupakan penelitian cross-sectional yang dilaksanakan pada April-Mei 2022 untuk menguji faktor sosial dan ekonomi dengan kecemasan persalinan. Mayoritas usia Ibu dan suami berada pada rentang 20-35 tahun, dengan pendidikan terakhir Sekolah Menengah ke Atas. Status bekerja Ibu didominasi oleh Ibu tidak bekerja atau Ibu rumah tangga sementara suami banyak bekerja di institusi non-pemerintah. Hanya sebagian Ibu menggunakan asuransi pribadi sebagai asuransi kesehatan dan transportasi umum untuk menuju ke fasilitas kesehatan. Dua dari faktor sosial dan ekonomi berpengaruh secara signifikan terhadap kecemasan persalinan yakni akses terhadap fasilitas kesehatan (.020, B: -.163) dan usia Ibu (.000, B: -.510). Jarak antara tempat tinggal menuju fasilitas kesehatan merupakan faktor sosial dan ekonomi yang berpengaruh terhadap kecemasan persalinan. Faktor lainnya memungkinkan Ibu untuk memiliki persiapan lebih baik dalam kehamilan dan proses persalinan.